Multidisciplinary Treatment of Colorectal Cancer Staging – Treatment – Pathology – Palliation - Baatrup, Gunnar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is intended as the equivalent of the Swiss Army knife for all members of colorectal cancer (CRC) multidisciplinary teams and those training in the fields of CRC management. It describes how to organize the team and explains the basic principles within the different disciplines involved in the treatment and care of CRC patients. Important, up-to-date knowledge is provided on visualization techniques, surgery, oncological treatment, palliation, and pathology, with special focus on controversies and aspects of interest to all team members. Care has been taken to ensure that each specialty-specific chapter will be approachable for team members from other specialties or professions, thereby facilitating an effective interdisciplinary approach to teamwork. The authors include leading European doctors and scientists who have influenced the development of the multidisciplinary team concept as well as other aspects of high-quality, individualized treatment of CRC patients.
Multidisciplinary treatment of colorectal cancer: Organizing the team -- Multidisciplinary treatment – influence on outcome. Surgery: Introduction to surgery -- Surgical anatomy of the rectum and the TEM specimen -- Low risk early rectal cancer -- High-risk early rectal cancer -- The total mesorectal excision -- Locally advanced rectal cancer and recurrence -- Reconstruction after neoadjuvant treatment and APR. Oncology: Introduction to oncology -- Chemotherapy for colon and rectum cancer -- Radiotherapy and radio-chemotherapy for rectal cancer -- Side effects from adjuvant and neoadjuvant treatment -- What should we do with complete responders. Imaging and staging: Introduction to imaging and staging -- MRI and CT for preoperative T and N staging of rectal cancer -- Transanal ultrasonography for rectal tumours. Pathology: Introduction to pathology -- Early colorectal cancer -- Quality of surgery – reporting on surgical specimen -- Pathological staging of colorectal cancer. The palliative team: Introduction to palliation -- Surgical treatment in palliative care -- Nausea. Recommendations: Patient related factors – patient’s preference -- Allocation to local treatment of rectal cancer.
Keywords: Oncology .; Surgical oncology; Pathology; Radiology; Oncology; Surgical Oncology; Pathology; Diagnostic Radiology